Preparation process of meta-aramid spinning solution
By using a composite catalyst formed by a polyphenol polymer skeleton, polydimethylsiloxane and an isocyanate coupling agent, the problems of low production efficiency and poor fiber performance caused by the lack of composite catalysts in the existing technology are solved, achieving More efficient polymerization and better fiber properties.
Patent Information
- Application Number
- CN202411037322.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The lack of composite catalyst system in the prior art leads to low production efficiency of meta-aramid fibers and poor fiber performance.
The polyphenol polymer skeleton is used to form a composite catalyst with polydimethylsiloxane and isocyanate coupling agent. Through the reaction with m-phenylenediamine and isophthaloyl chloride, a stable composite structure is formed to promote the polymerization reaction. Uniformity and efficiency.
It improves the uniformity of the molecular weight and molecular weight distribution of the polymer, enhances the mechanical properties and thermal stability of the fiber, and improves the performance of the spinning solution and the quality of the fiber.
Smart Images

Figure CN119332366A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spinning solution, in particular to a preparation process of meta-aramid spinning solution. Background Art
[0002] Meta-aramid, also known as polyisophthalamide (m-phenylene diamine) fiber, is made by polycondensation of isophthaloyl chloride (IPC) and m-phenylene diamine (MPD). As a high-temperature resistant fiber that was developed early, widely used, mass-produced and rapidly developed, it has occupied an important position in the field of special fibers, and its total output ranks second. The molecular structure of meta-aramid fiber is:
[0003]
[0004] Meta-aramid is a linear macromolecule composed of meta-phenyl groups connected to each other by amide groups. In its crystal, hydrogen bonds exist on two planes, such as a lattice arrangement, thus forming a three-dimensional structure of hydrogen bridges. Due to the strong effect of hydrogen bonds, the chemical structure of meta-aramid is stable, and it has excellent heat resistance, flame retardancy, chemical corrosion resistance, electrical insulation and mechanical properties. It is an indispensable basic material in high-tech industries such as aerospace, military fire protection, electronic communications, energy conservation and environmental protection, and petrochemicals. The glass transition temperature Tg of meta-aramid fiber is 270℃, and no significant decomposition or carbonization will occur below 350℃. In addition, when the ambient temperature exceeds 400℃, the fiber will gradually lose its toughness, carbonize and eventually decompose, but in this process, it will not produce droplets, thereby reducing the risk of fire. The production process of meta-aramid mainly includes two production processes: spinning solution preparation (polymerization process) and spinning, and the quality and stability of the spinning solution directly affect the stability of the spinning process and the quality of the fiber.
[0005] The invention patent with publication number CN109400873A discloses a continuous polymerization method for preparing high-performance poly(m-phenylene isophthalamide), including prepolymerization, neutralization, polymerization, neutralization, and filtering processes, and performs continuous low-temperature solution polymerization, which has the advantages of stable polymerization conditions, low energy consumption, and low investment. The invention patent with publication number CN116813902A discloses a poly(m-phenylene isophthalamide) solution, meta-aramid spinning solution and its preparation method, which can also achieve low viscosity by using another compound to replace dimethylacetamide (DMAC) as a solvent, allowing production in a continuous manner, and can be used as meta-aramid spinning solution. However, catalysts are usually not used or only a single catalyst is used, such as acidic catalysts, alkaline catalysts or metal complexes, resulting in a slow reaction speed, requiring a longer time to reach the required conversion rate, reducing production efficiency, and causing unnecessary side reactions, thereby affecting the properties of the spun fibers. Summary of the invention
[0006] In order to solve the problems mentioned in the above background technology, such as lack of composite catalyst system and poor fiber performance, the present invention provides a process for preparing meta-aramid spinning solution.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A process for preparing a meta-aramid spinning solution comprises the following steps:
[0009] S1. Pass metaphenylenediamine (MPD) into the tower kettle, start the vacuum unit, slowly start the heat transfer oil, heat the tower kettle to the specified temperature, and when the light component storage tank reaches 30% liquid level, turn on the bottom liquid pump to reflux to the tower, control the reflux flow rate for full reflux, remove high-boiling tar-like impurities, observe the color of the material in the tower discharge sight glass, open the discharge valve to feed the finished product metering tank, if the MPD purity is ≥99.98%, continue to discharge, and pump the decolorized MPD into the storage tank. If it does not reach the target, return to the tower kettle to continue decolorization. Among them, the waste gas generated by the decolorization of metaphenylenediamine is mainly metaphenylenediamine. After the decolorization waste gas is collected under negative pressure, it enters the polymerization workshop and the front-end tail gas treatment system of the spinning workshop, and is discharged to high altitude after treatment. The residue produced by vacuum distillation is mainly composed of metaphenylenediamine and organic impurities, which are collected and centrally disposed of;
[0010] S2, transporting the decolorized m-phenylenediamine from a storage tank to a blending tank through a pipeline, first adding dimethylacetamide (DMAC) to dissolve it and then passing it into a reactor, then adding isophthaloyl chloride into the reactor through a pipeline, and controlling the reaction conditions under a nitrogen atmosphere to perform a prepolymerization reaction to generate oligomers and hydrogen chloride, neutralizing the hydrogen chloride for the first time, and performing a first filter press with a plate and frame filter press;
[0011] S3. Continue to add isophthaloyl chloride to the filtered oligomer, and under the same conditions as the prepolymerization reaction, introduce a composite catalyst to carry out a post-condensation reaction to generate polyisophthaloyl chloride metaphenylenediamine and a small amount of hydrogen chloride, and neutralize the hydrogen chloride for a second time to obtain a neutralized polymer slurry, which enters a stock solution storage tank through a plate and frame filter press, recovers DMAC and the catalyst, and obtains a meta-aramid spinning stock solution.
[0012] Preferably, in step S1, the temperature of the bottom of the tower is 190-200° C., and the pressure is (-0.09)-(-0.1) MPa. When the color of the material turns grayish white, full reflux is performed for another 2-3 hours.
[0013] Preferably, the pressure of the prepolymerization reaction in step S2 is normal pressure, and the reaction temperature is (-10)-30°C.
[0014] Furthermore, the pH value of the system is controlled to be less than 7 during the first neutralization and the second neutralization. Ammonia vapor is used for the first neutralization. The ammonia vapor is directly introduced into the cylinder through a pipeline after being gasified from liquid ammonia. Hydrogen chloride reacts with ammonia vapor to generate microcrystalline ammonium chloride. After the ammonium chloride crystals are separated by a plate-frame filter press, the ammonium chloride is collected in a closed room of a post-processing workshop for drying and recovery. Diethylamine is used for the second neutralization. The barreled diethylamine is pumped into a mixing tank and then into a neutralization kettle. After neutralization, a small amount of diethylamine salt is generated and dissolved in a DMAC solution. The diethylamine is recovered and used for the preparation of a composite catalyst. The plate-frame filter press is used for the second plate-frame filter press to filter out the ammonium chloride that has not been completely filtered.
[0015] Preferably, in step S3, the molar ratio of the oligomer to isophthaloyl chloride is 1:(0.8-1), and the content of the composite catalyst is 2-5wt%.
[0016] Furthermore, the composite catalyst in step S3 is prepared by the following steps:
[0017] A1. Under an inert atmosphere, a phenolic compound is dissolved in excess ethanol, ferric chloride is added, and the mixture is stirred at 60-70° C. for 4-10 hours, and the solvent is removed by rotary evaporation to obtain a polyphenol polymer, the average molecular weight of which is 4000-7000 g / mol as determined by gel permeation chromatography;
[0018] A2. Add the polyphenol polymer to excess tetrahydrofuran, add polydimethylsiloxane and isocyanate coupling agent, stir and react at 70-80°C for 2-4h, add ethylenediamine and 4-dimethylaminopyridine while hot, stir and react at room temperature for 24-48h, remove impurities, wash with ethanol 3-5 times, vacuum dry at 60-80°C for 12-48h, and heat treat at 200-300°C for 1-4h under an inert atmosphere to obtain a composite catalyst.
[0019] Preferably, the mass ratio of the phenolic compound to ferric chloride is (5-7):(0.8-1.2).
[0020] Preferably, the phenolic compound is one of indan bisphenol, phloroglucinol, catechol, xylenol, 3-isopropylphenol and p-cresol.
[0021] Preferably, the mass ratio of the polyphenol polymer, polydimethylsiloxane and isocyanate coupling agent is (10-15):(4-8):(1-3), and the mass ratio of ethylenediamine and 4-dimethylaminopyridine is (8-13):(2-4).
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. In the technical solution of the present invention, the polyphenol polymer skeleton is mainly composed of phenolic hydroxyl (-OH) groups, which form abundant active sites on the molecular chain and can react chemically with polydimethylsiloxane (PDMS) and isocyanate coupling agents to construct a stable composite structure. The specific reaction includes the reaction between hydroxyl and ethylenediamine and isocyanate (-NCO) to generate carbamate (-NHCOO-) bonds, thereby enhancing the stability of the polymer skeleton. The reaction equation is:
[0024] Ar-OH+R-NCO→Ar-NHCOOR
[0025] NH2R+R'-NCO→NHCOOR′
[0026] The phenolic hydroxyl groups of the polyphenol polymer and the urethane bonds formed by the reaction of ethylenediamine and isocyanate, as well as the introduction of PDMS segments, form a three-dimensional cross-linked network. This enhances the mechanical strength and thermal stability of the catalyst, and also provides abundant active sites to promote the adsorption and activation of reactants. PDMS, as a flexible segment, enhances the flexibility and solubility of the catalyst through silicon-oxygen bonds (Si-O-Si), helps to evenly disperse the catalyst in the reaction system, and improves the overall catalytic efficiency.
[0027] 2. The composite catalyst forms an intermediate complex with m-phenylenediamine and isophthaloyl chloride, and reduces the activation energy of the reaction through coordination. The specific process is as follows:
[0028] Ar-NH2+ClCO-Ar-COCl→Ar-NH-CO-Ar-CO-NH-Ar
[0029] Among them, the ligand stabilizes the intermediate complex, reduces the free energy barrier of the reaction, and accelerates the polymerization reaction. In addition, the unique structure on the catalyst surface guides the reactants to arrange in a specific direction. The specific structure is as follows: -(Ar-NH-CO-Ar-CO-) n , which helps to form regular polymer chains and improve the molecular weight of the polymer and its uniformity of distribution. At the same time, the PDMS chain segments stabilize the reaction intermediates and transition states through steric hindrance and coordination to prevent side reactions. One of the reaction equations is:
[0030] Ar-NH-CO-Ar-CO-NH-Ar+Ar-NH2→Ar-NH-CO-Ar-CO-NH-Ar-NH2
[0031] During this process, the PDMS chain segments provide effective spatial protection, avoid unnecessary side reactions, and improve selectivity and efficiency.
[0032] 3. By decolorizing m-phenylenediamine, high-boiling tar-like impurities are effectively removed, significantly improving the purity of the raw materials, which is not only conducive to the subsequent polymerization reaction, but also can improve the quality of the final product. High-purity m-phenylenediamine can reduce side reactions during the polymerization process, making the polymerization reaction more controllable, and thus obtaining meta-aramid with better performance.
[0033] 4. Effectively recovering and utilizing DMAC, ethylenediamine and catalysts not only reduces production costs, but also reduces environmental pollution. The recovered DMAC and catalysts can be reused in polymerization reactions, and the recovered ethylenediamine can be used in the production of catalysts, thus realizing the recycling of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is a process flow chart for preparing meta-aramid spinning solution. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the raw materials used in the present invention are all derived from conventional products purchased on the market.
[0037] Preparation Example 1
[0038] The composite catalyst comprises the following steps to prepare:
[0039] A1. Under an inert atmosphere, 5 kg of p-cresol was dissolved in excess ethanol, 0.8 kg of ferric chloride was added, and the mixture was stirred at 60° C. for 4 h. The solvent was removed by rotary evaporation to obtain a polyphenol polymer;
[0040] A2. Add 10 kg of polyphenol polymer to excess tetrahydrofuran, add 4 kg of polydimethylsiloxane and 1 kg of toluene diisocyanate, stir and react at 70 ° C for 2 h, add 8 kg of ethylenediamine and 2 kg of 4-dimethylaminopyridine while hot, stir and react at room temperature for 24 h, remove impurities, wash with ethanol 3 times, vacuum dry at 60 ° C for 12 h, and heat treat at 200 ° C for 1 h under an inert atmosphere to obtain a composite catalyst.
[0041] Preparation Example 2
[0042] The composite catalyst comprises the following steps to prepare:
[0043] A1. Under an inert atmosphere, 6 kg of p-cresol was dissolved in excess ethanol, 1 kg of ferric chloride was added, and the mixture was stirred at 65° C. for 7 h. The solvent was removed by rotary evaporation to obtain a polyphenol polymer;
[0044] A2. Add 12.5 kg of polyphenol polymer to excess tetrahydrofuran, add 6 kg of polydimethylsiloxane and 2 kg of toluene diisocyanate, stir and react at 75 ° C for 3 hours, add 10.5 kg of ethylenediamine and 3 kg of 4-dimethylaminopyridine while hot, stir and react at room temperature for 36 hours, remove impurities, wash with ethanol 4 times, vacuum dry at 70 ° C for 24 hours, and heat treat at 250 ° C for 2.5 hours under an inert atmosphere to obtain a composite catalyst.
[0045] Preparation Example 3
[0046] The composite catalyst comprises the following steps to prepare:
[0047] A1. Under an inert atmosphere, 7 kg of xylenol was dissolved in excess ethanol, 1.2 kg of ferric chloride was added, and the mixture was stirred at 70° C. for 10 h, and the solvent was removed by rotary evaporation to obtain a polyphenol polymer;
[0048] A2. Add 15 kg of polyphenol polymer to excess tetrahydrofuran, add 8 kg of polydimethylsiloxane and 3 kg of toluene diisocyanate, stir and react at 80 ° C for 4 hours, add 13 kg of ethylenediamine and 4 kg of 4-dimethylaminopyridine while hot, stir and react at room temperature for 48 hours, remove impurities, wash with ethanol 5 times, vacuum dry at 80 ° C for 48 hours, and heat treat at 300 ° C for 4 hours under an inert atmosphere to obtain a composite catalyst.
[0049] Example 1
[0050] A process for preparing a meta-aramid spinning solution comprises the following steps:
[0051] S1. Pass 3 tons of MPD into the tower kettle, turn on the vacuum unit, pump the negative pressure to -0.09MPa, slowly turn on the heat transfer oil, heat the tower kettle to 190℃, when the light component storage tank reaches 30% liquid level, turn on the bottom liquid pump to reflux to the tower, control the reflux flow rate for full reflux, remove high-boiling tar-like impurities, observe the color of the material in the tower discharge sight glass, when the color of the material turns grayish white, reflux for another 2h. Open the discharge valve to feed the finished product metering tank. If the MPD purity is ≥99.98%, continue to discharge and pump the decolorized MPD into the storage tank. If it does not reach the purity, return to the tower kettle to continue decolorization;
[0052] S2, transporting the decolorized m-phenylenediamine from a storage tank to a blending tank through a pipeline, first adding an excess of dimethylacetamide (DMAC) to dissolve it and then passing it into a reactor, then adding 10wt% of isophthaloyl chloride into the reactor through a pipeline, controlling the reaction temperature to -10°C under a nitrogen atmosphere, and performing a prepolymerization reaction at normal pressure to generate oligomers and hydrogen chloride, neutralizing the hydrogen chloride for the first time with ammonia vapor, and performing a first pressure filtration with a plate and frame filter press;
[0053] S3. Continue to add isophthaloyl chloride to the filtered oligomer in a molar ratio of 1:0.8, and under the same conditions as the prepolymerization reaction, introduce 2wt% of the composite catalyst prepared in Preparation Example 1 to carry out a post-condensation reaction to generate polyisophthaloyl chloride metaphenylenediamine and a small amount of hydrogen chloride, and neutralize the hydrogen chloride for a second time with ethylenediamine to obtain a neutralized polymer slurry, which enters a stock solution storage tank through a plate and frame filter press to obtain a meta-aramid spinning stock solution.
[0054] Example 2
[0055] A process for preparing a meta-aramid spinning solution comprises the following steps:
[0056] S1. Pass 3 tons of MPD into the tower kettle, turn on the vacuum unit, pump the negative pressure to -0.097MPa, slowly turn on the heat transfer oil, heat the tower kettle to 198℃, when the light component storage tank reaches 30% liquid level, turn on the bottom liquid pump to reflux to the tower, control the reflux flow rate for full reflux, remove high-boiling tar-like impurities, observe the color of the material in the tower discharge sight glass, when the color of the material turns grayish white, reflux for another 2.5h. Open the discharge valve to feed the finished product metering tank. If the MPD purity is ≥99.98%, continue to discharge and pump the decolorized MPD into the storage tank. If it does not reach the purity, return to the tower kettle to continue decolorization;
[0057] S2, transporting the decolorized m-phenylenediamine from a storage tank to a blending tank through a pipeline, first adding an excess of dimethylacetamide (DMAC) to dissolve it and then passing it into a reactor, then adding 15wt% of isophthaloyl chloride into the reactor through a pipeline, and in a nitrogen atmosphere, controlling the reaction temperature to 5°C, performing a prepolymerization reaction at normal pressure to generate oligomers and hydrogen chloride, neutralizing the hydrogen chloride for the first time with ammonia vapor, and performing a first pressure filtration with a plate and frame filter press;
[0058] S3. Continue to add isophthaloyl chloride to the filtered oligomer in a molar ratio of 1:0.9, and under the same conditions as the prepolymerization reaction, introduce 3.5wt% of the composite catalyst prepared in Preparation Example 2 to carry out a post-condensation reaction to generate polyisophthaloyl chloride metaphenylenediamine and a small amount of hydrogen chloride, and neutralize the hydrogen chloride for a second time with ethylenediamine to obtain a neutralized polymer slurry, which enters a stock solution storage tank through a plate and frame filter press to obtain a meta-aramid spinning stock solution.
[0059] Example 3
[0060] A process for preparing a meta-aramid spinning solution comprises the following steps:
[0061] S1. Pass 3 tons of MPD into the tower kettle, turn on the vacuum unit, pump the negative pressure to -0.99MPa, slowly turn on the heat transfer oil, heat the tower kettle to 199℃, when the light component storage tank reaches 30% liquid level, turn on the bottom liquid pump to reflux to the tower, control the reflux flow rate for full reflux, remove high-boiling tar-like impurities, observe the color of the material in the tower discharge sight glass, when the color of the material turns grayish white, reflux for another 3 hours. Open the discharge valve to feed the finished product metering tank. If the MPD purity is ≥99.98%, continue to discharge and pump the decolorized MPD into the storage tank. If it does not reach the purity, return to the tower kettle to continue decolorization;
[0062] S2, transporting the decolorized m-phenylenediamine from a storage tank to a blending tank through a pipeline, first adding an excess of dimethylacetamide (DMAC) to dissolve it and then passing it into a reactor, then adding 18 wt % of isophthaloyl chloride into the reactor through a pipeline, controlling the reaction temperature to 10° C. under a nitrogen atmosphere, performing a prepolymerization reaction at normal pressure to generate oligomers and hydrogen chloride, neutralizing the hydrogen chloride for the first time with ammonia vapor, and performing a first pressure filtration with a plate and frame filter press;
[0063] S3. Continue to add isophthaloyl chloride to the filtered oligomer in a molar ratio of 1:0.98, and under the same conditions as the prepolymerization reaction, introduce 4wt% of the composite catalyst prepared in Preparation Example 3 to carry out a post-condensation reaction to generate polyisophthaloyl chloride metaphenylenediamine and a small amount of hydrogen chloride, and neutralize the hydrogen chloride for a second time with ethylenediamine to obtain a neutralized polymer slurry, which enters a stock solution storage tank through a plate and frame filter press to obtain a meta-aramid spinning stock solution.
[0064] Example 4
[0065] A process for preparing a meta-aramid spinning solution comprises the following steps:
[0066] S1. Pass 3 tons of MPD into the tower kettle, turn on the vacuum unit, pump the negative pressure to -0.1MPa, slowly turn on the heat transfer oil, heat the tower kettle to 200℃, when the light component storage tank reaches 30% liquid level, turn on the bottom liquid pump to reflux to the tower, control the reflux flow rate for full reflux, remove high-boiling tar-like impurities, observe the color of the material in the tower discharge sight glass, when the color of the material turns grayish white, reflux for another 3h. Open the discharge valve to feed the finished product metering tank. If the MPD purity is ≥99.98%, continue to discharge and pump the decolorized MPD into the storage tank. If it does not reach the level, return to the tower kettle to continue decolorization;
[0067] S2, transporting the decolorized m-phenylenediamine from the storage tank to the blending tank through a pipeline, first adding an excess of dimethylacetamide (DMAC) to dissolve it and then passing it into the reactor, then adding 20wt% of isophthaloyl chloride into the reactor through a pipeline, controlling the reaction temperature to 30°C under a nitrogen atmosphere, performing a prepolymerization reaction under normal pressure to generate oligomers and hydrogen chloride, neutralizing the hydrogen chloride for the first time with ammonia vapor, and performing a first pressure filtration with a plate and frame filter press;
[0068] S3. Continue to add isophthaloyl chloride to the filtered oligomer in a molar ratio of 1:1, and under the same conditions as the prepolymerization reaction, introduce 5wt% of the composite catalyst prepared in Preparation Example 3 to carry out a post-condensation reaction to generate polyisophthaloyl chloride metaphenylenediamine and a small amount of hydrogen chloride, and neutralize the hydrogen chloride for a second time with ethylenediamine to obtain a neutralized polymer slurry, which enters a stock solution storage tank through a plate and frame filter press to obtain a meta-aramid spinning stock solution.
[0069] Comparative Example 1
[0070] The difference between this comparative example and preparation example 1 is that no phenolic compound is added, and the remaining steps are the same as those in example 1.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Preparation Example 2 is that polydimethylsiloxane is not added, and the remaining steps are the same as Example 2.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Preparation Example 3 is that no isocyanate coupling agent is added, and the remaining steps are the same as Example 3.
[0075] Comparative Example 4
[0076] The difference between this comparative example and preparation example 1 is that ethylenediamine is not added, and the remaining steps are the same as those in example 1.
[0077] Comparative Example 5
[0078] The difference between this comparative example and Example 1 is that the composite prepared in Comparative Example 1 is used, and the remaining steps are the same as those in Example 1.
[0079] Comparative Example 6
[0080] The difference between this comparative example and Example 2 is that the composite prepared in Comparative Example 2 is used, and the remaining steps are the same as those in Example 2.
[0081] Comparative Example 7
[0082] The difference between this comparative example and Example 3 is that the composite prepared in Comparative Example 3 is used, and the remaining steps are the same as those in Example 3.
[0083] Comparative Example 8
[0084] The difference between this comparative example and Example 4 is that the composite prepared in Comparative Example 4 is used, and the remaining steps are the same as those in Example 4.
[0085] According to the preparation methods of Examples 1-4 and Comparative Examples 5-8, continuous meta-aramid spinning solution production was carried out for 12 hours, and 500 g of the sample was randomly selected as a sample for performance testing. The results are shown in Table 1:
[0086] Table 1. Test results of stock solution performance of Examples 1-4 and Comparative Examples 5-8
[0087]
[0088] The viscosity was measured by a viscometer, the molecular weight distribution was measured by gel permeation chromatography (Waters Alliance e2695 GPC / SEC system), and the thermal stability was measured by thermogravimetric analysis (TGA PT1600).
[0089] Each sample was spun to obtain a product specification of 3.56 dtex×69 mm. Referring to GB / T 31889-2015 "Meta-aramid Staple Fibers", the quality of the spun fibers was evaluated. The results are shown in Table 2:
[0090] Table 2. Fiber performance test results of Examples 1-4 and Comparative Examples 5-8
[0091]
[0092] As can be seen from Table 1, the viscosity of the embodiments is generally higher than that of the comparative examples, which may be because the addition of the composite catalyst increases the molecular weight of the polymer, thereby increasing the viscosity of the stock solution. Viscosity is an important factor affecting spinning performance, and a higher viscosity generally means better spinning performance. The molecular weight distribution (Mw / Mn) of the embodiments is relatively narrower, indicating that the polymer molecular chain is more uniform, which helps to improve the quality and performance of the spun fiber. The molecular weight distribution is wider in the comparative examples, which may be due to the lack of the regulatory effect of the composite catalyst. The thermal stability temperature of the embodiments is higher, indicating that the composite catalyst may improve the thermal stability of the polymer, which is very important for heat resistance during the spinning process.
[0093] As can be seen from Table 2, the breaking strength of the embodiment is significantly higher than that of the comparative example, which may be due to the fact that the addition of the composite catalyst enhances the strength and uniformity of the polymer chain. The linear density deviation rate and length deviation rate of the embodiment are better than those of the comparative example, indicating that the uniformity and consistency of the fiber are improved after the use of the composite catalyst. The ultra-long fiber rate and double-length fiber content of the embodiment are low, indicating that the fiber length is more uniform, which is beneficial to improving the processing performance of the fiber and the quality of the final product. The defect content difference between the samples is not large, but the embodiment is slightly better than the comparative example, indicating that the composite catalyst may be helpful in reducing defects. The dry heat shrinkage rate of the embodiment is significantly lower than that of the comparative example, indicating that the composite catalyst may improve the thermal stability of the fiber.
[0094] The composite catalyst added in Examples 1-4 may improve the uniformity and efficiency of the polymerization reaction, thereby improving the molecular weight of the polymer and the uniformity of the molecular weight distribution, thereby enhancing the mechanical properties and thermal stability of the fiber. The components such as polyphenol polymer, polydimethylsiloxane, toluene diisocyanate and ethylenediamine in the composite catalyst may produce a synergistic effect, jointly promoting the growth and uniformity of the polymer chain. Due to the improvement in the performance of the stock solution, the uniformity and consistency of the fiber in the spinning process are improved, thereby affecting the various performance indicators of the final fiber product. In addition, the comparative example may not fully react within the specified time, resulting in a large difference in performance compared to the embodiment.
[0095] In summary, by comparing and analyzing the stock solution performance and fiber performance data of the embodiments and the comparative examples, it can be inferred that the meta-aramid spinning stock solutions prepared in Examples 1-4 have good performance and can improve the quality and performance of the fibers while improving production efficiency.
[0096] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for preparing a meta-aramid spinning solution, characterized in that: The following steps are involved: S1, passing m-phenylenediamine into the kettle, decolorizing it by vacuum distillation, and removing high-boiling tar-like impurities by total reflux separation to obtain decolorized m-phenylenediamine with a purity of ≥99.98%; S2, dissolving the decolorized m-phenylenediamine in dimethylacetamide, then feeding isophthaloyl chloride into a reactor through a pipeline, controlling the reaction conditions under an inert atmosphere, performing a prepolymerization reaction, and neutralizing the hydrogen chloride for the first time; S3. Continue to add isophthaloyl chloride to the filtered oligomer, introduce the composite catalyst under the same conditions as the prepolymerization reaction, carry out post-polycondensation reaction, neutralize the hydrogen chloride for the second time to obtain a neutralized polymer slurry, and pass it into a stock solution storage tank through a filter press to obtain meta-aramid spinning stock solution.
2. The process for preparing a meta-aramid spinning solution according to claim 1, characterized in that: In step S1, the temperature of the kettle is 190-200°C, and the pressure is (-0.09)-(-0.1) MPa. When the color of the material turns grayish white, it is fully refluxed for 2-3 hours.
3. The process for preparing a meta-aramid spinning solution according to claim 1, characterized in that: The pressure of the prepolymerization reaction in step S2 is normal pressure, and the reaction temperature is (-10)-30°C.
4. The process for preparing a meta-aramid spinning solution according to claim 1, characterized in that: The pH value of the system is controlled to be less than 7 during the first neutralization and the second neutralization. Ammonia vapor is used for the first neutralization and diethylamine is used for the second neutralization.
5. The process for preparing a meta-aramid spinning solution according to claim 1, characterized in that: In step S3, the molar ratio of the oligomer to isophthaloyl chloride is 1:(0.8-1), and the content of the composite catalyst is 2-5wt%.
6. The process for preparing a meta-aramid spinning solution according to claim 1, characterized in that: The composite catalyst in step S3 comprises the following steps to prepare: A1. Under an inert atmosphere, a phenolic compound is dissolved in excess ethanol, ferric chloride is added, and the mixture is stirred at 60-70° C. for 4-10 hours, and the solvent is removed by rotary evaporation to obtain a polyphenol polymer; A2. Add the polyphenol polymer to excess tetrahydrofuran, add polydimethylsiloxane and isocyanate coupling agent, stir and react at 70-80°C for 2-4h, add ethylenediamine and 4-dimethylaminopyridine while hot, stir and react at room temperature for 24-48h, remove impurities, wash with ethanol 3-5 times, vacuum dry at 60-80°C for 12-48h, and heat treat at 200-300°C for 1-4h under an inert atmosphere to obtain a composite catalyst.
7. The process for preparing meta-aramid spinning solution according to claim 6, characterized in that: The mass ratio of the phenolic compound to ferric chloride is (5-7):(0.8-1.2).
8. The process for preparing meta-aramid spinning solution according to claim 6, characterized in that: The phenolic compound is one of indanyl bisphenol, phloroglucinol, catechol, xylenol, 3-isopropylphenol and p-cresol.
9. The process for preparing a meta-aramid spinning solution according to claim 6, characterized in that: The mass ratio of the polyphenol polymer, polydimethylsiloxane and isocyanate coupling agent is (10-15): (4-8): (1-3), and the mass ratio of ethylenediamine and 4-dimethylaminopyridine is (8-13): (2-4).
Citation Information
Patent Citations
Method for continuous production of polyisophthaloyl metaphenylene diamine spinning stock solution
CN102517677A
Continuous polymerization method for preparing high-performance polyisophthaloyl metaphenylene diamine
CN109400873A
Method and device for preparing modified meta-aramid fiber through continuous polymerization-dry-wet spinning
CN113774509A
Meta-aramid fiber as well as molecular weight regulation and control method and application thereof
CN116695270A
Polyisophthaloyl metaphenylene diamine solution, meta-aramid fiber spinning solution and preparation method of poly (isophthaloyl metaphenylene diamine) solution and meta-aramid fiber spinning solution
CN116813902A